An Exploration in the Theory of Exchange-Rate Regimes - Helpman, Elhanan (Journal of Political Economy, 1981)
Three exchange-rate regimes–a float, a one-sided peg, and a cooperative peg–are evaluated and compared in terms of efficiency and welfare levels. The framework of analysis embodies country-specific monies, with the money of each country being used to transact in its commodity markets and its currency-denominated bonds. Welfare levels depend only on consumption levels. In the presence of perfect foresight all equilibrium allocations are Pareto efficient. In a floating exchange-rate regime the perfect foresight equilibrium allocation coincides with an equilibrium of a costless barter economy. The same result holds in a one-sided peg if the pegging country's exchange-rate stabilizing authority breaks even over time. In a cooperative peg regime there is a different equilibrium allocation for each combination of exchange-rate levels and monetary policies. Problems of policy coordination and conflicts in desired monetary policies are discussed.